2014
DOI: 10.12691/ajcea-2-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fibers and Fly Ash on Mechanical Properties of Concrete

Abstract: The Present study was carried out to evaluate the influence of addition of Fibres and Class 'C' Flyash on the mechanical properties of concrete. Fibre Reinforced Concrete (FRC) is very useful in extreme climate where shrinkage of concrete causes cracks. The Fibre Reinforced Flyash concrete (FRFAC) has been successfully used to minimize cavitations / damages in hydraulics structures. The FRC with and without Fly ash was tested with the fraction of volume of the steel Fibre in concrete which varied from 0.0 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Akhtar and Akhtar [15] carried out a study to investigate the effect of adding fibers and Class 'C' fly ash on the mechanical properties of concrete. Akhtar et al [16] showed that behavior of recycled demolished concrete with partial replacement of cement by recycled remains is almost similar to that of conventional concrete. Recycling will not only preserve the natural resources, but will also obtain more economic use of such concrete, which is a good step toward sustainability around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Akhtar and Akhtar [15] carried out a study to investigate the effect of adding fibers and Class 'C' fly ash on the mechanical properties of concrete. Akhtar et al [16] showed that behavior of recycled demolished concrete with partial replacement of cement by recycled remains is almost similar to that of conventional concrete. Recycling will not only preserve the natural resources, but will also obtain more economic use of such concrete, which is a good step toward sustainability around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Natural human hair fibers is another additive that investigated by some other researchers to study the effects on mechanical soil properties. Human hair fibers have a good tensile strength which is same as that of strength of copper wire of same diameter [8]. Reference [9] have studied on present's characterization of human hair fiber-reinforced sand using direct shear tests under dry and saturated conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Human hair fibres have a good elongation strength which is same as that of strength of copper wire of same diameter (Akhtar, Ahmad 2009). Hair is a non-biodegradable solid waste material which generate an environmental problem in disposal.…”
Section: Introductionmentioning
confidence: 99%